Courseware for Driving Simulation - Chew Sin, Seng (2013)
This project is to develop a Courseware of Driving Simulation. Driving simulation is a simulation of driving environment. Driving simulation is useful but not commonly used by driver for driving learning purpose. Thus, the car driving accidents increase sharply. Main purpose for develop the courseware of driving simulation is to decreasing car driving accident case and provide a platform to driver for training their own driving skill. The new driving simulation software will be providing a serious game training on driving skill. User will use either keyboard or other hardware to control the car and multiple driving learning courses will be providing inside the simulation. At the end of the simulation process, result of evaluating the performance during the course will be shown. In a nutshell, user can review their result and realise which driving skill is their weakness thus can improve their skill.